The function of hotels in revitalizing rural areas: case studies in Pomerania Province - Katarzyna Leśniewska-Napierała; Tomasz Napierała (Tourism, 2017)
This article indicates optimal local, social, economic and geographical relationships contributing to the effective implementation of hotel investment as a part of rural area revitalisation. This will be undertaken through the case studies of four hotels functioning in revitalized historical buildings in the rural areas of Pomerania Province. A ‘multiple case study’ will be performed based on the following methods: 1) the desk study of the data concerning the activity of the hotels; 2) a micro- and meso-scale cartographic inventory; 3) structured individual in-depth interviews with hotel owners and managers, as well as with the authorities and officials responsible for the promotion of the communes where the hotels are situated.